Effect of blast and gas pressure on debris launching velocity under internal detonation - Yu, Qing Jun (2011)
Debris launching velocity is one of the major parameters in determining the debris hazard zone caused by accidental detonation of ammunition in a magazine. Upon detonation, the explosive generates a blast pressure. In tandem, gas pressure is also created due to accumulation of the gaseous products with high temperature produced by the explosion. It may cause the structural breakup and then exerts impulse on the debris. The impulse makes debris fly with an initial velocity. Subsequently, the pressure propels the debris to fly faster and accelerate until the overpressure (over the ambient pressure) drops to zero. After that, the debris continues to fly but slows down due to the frictional drag by the surrounding air. This paper presents a study to differentiate the effects of blast pressure and gas pressure on the debris launching velocity. Numerical simulations for a series of defined cases under different conditions are carried out. To begin, two basic and extreme cases are investigated. The first case is to detonate the explosive put inside a fully-constraint cubicle to evaluate the gas pressure. The second case is to detonate the explosive in an open space to evaluate the blast pressure. Then, a typical setup is used to evaluate the debris launching velocities under the effects of both blast pressure and gas pressure. In the numerical simulations, the high explosive (HE) and the air are modeled using Arbitrary-Lagrangian-Eulerian (ALE) multi-material formulations while the fluid-debris interaction is simulated via coupling techniques for fluid-structure interaction (FSI). Simulation results yield relatively good agreement with those obtained from experiments and empirical equations. It provides insight and explanations for the debris launching process which is hardly observed in the experiments. This study verifies the different effects on the resulting debris launching velocity due to the blast pressure and the gas pressure. It also shows that the gas pressure has dominant effect on the debris launching velocity.